2022
DOI: 10.3390/ma15072701
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Freeze–Thaw Cycles on the Mechanical Properties of Highly Rubberised Asphalt Mixtures Made with Warm and Cold Asphalt Binders

Abstract: The present study has been developed to investigate the effect of freeze and thaw (F–T) cycles on the characteristics of highly rubberised asphalt materials to be used as impact-absorbing pavement (IAP) in urban road infrastructures. The tested samples were produced in the laboratory following the dry process incorporation. Two main types of crumb rubber particles in the range of 0–4 mm were used. Moreover, two types of binders, one warm and one cold, were utilised to prove the feasibility of cold-produced adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Preliminary studies have confirmed the feasibility and potential effectiveness of the impact-absorbing pavements (IAP) starting from various mix designs, using both warm [8,[10][11][12] and cold bituminous binders [13]; during their development process, a complete mechanical analysis of the material was required to assess their attenuation properties. The uniaxial compression test in different setups has usually been adopted to investigate the basic loading and relaxation behaviour of these materials [6,7] because the methods commonly used for traditional asphalt, like the ITSM test (EN 12697-26), are not able to describe the considerable soft behaviour of the samples.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies have confirmed the feasibility and potential effectiveness of the impact-absorbing pavements (IAP) starting from various mix designs, using both warm [8,[10][11][12] and cold bituminous binders [13]; during their development process, a complete mechanical analysis of the material was required to assess their attenuation properties. The uniaxial compression test in different setups has usually been adopted to investigate the basic loading and relaxation behaviour of these materials [6,7] because the methods commonly used for traditional asphalt, like the ITSM test (EN 12697-26), are not able to describe the considerable soft behaviour of the samples.…”
Section: Introductionmentioning
confidence: 99%